Systematic review of strategies for improving attendance in health and mental health interventions for children and adolescents in LMICs: Implications for mental health interventions - Anna A. Peycheva; Anthony F. Guevara; Mark J.D. Jordans (Elsevier, 2023)
This review synthesises the evidence base for promoting and maintaining attendance in mental health and health interventions for children and adolescents in low- and middle-income countries (LMIC) and identifies strategies that can be employed for mental health interventions in those contexts. This is achieved through systematically searching relevant peer-reviewed literature in PubMed, Embase, PsychINFO and Global Health. Retrieved studies are screened by title and abstract, and subsequently the relevant papers undergo a full-text screening. The quality of the included studies is assessed using validated quality appraisal tools, namely the JBI Critical Appraisal Checklist and the Mixed Methods Appraisal Tool, and key data is extracted from each of the included studies. Fifteen studies from twelve different countries meet the eligibility criteria. The mean age of the participants in each study falls between 9 and 18 years. Only one study focuses on a mental health intervention, while the majority test strategies for health interventions. Six distinct categories of attendance promotion strategies are identified: (i) service improvement, (ii) health education and (iii) peer-support are the three most utilised strategies, followed by (iv) community engagement, (v) counselling, and (vi) cash-based approaches. Ten out of the fifteen studies (66.7%) yield statistically significant results for the improvement of attendance outcomes, one (6.7%) does not find any statistical significance and four (26.7%) do not test effectiveness of the strategies. While these results highlight a need for further studies with rigorous methodologies focusing on testing the effectiveness of strategies, service improvement and community engagement were noted as particularly effective. The findings identify several promising strategies from the global health literature, which can be translated to mental health interventions for children and adolescents in LMICs. Nevertheless, further research is necessary to establish their appropriateness in addressing the barriers to attendance in mental health interventions.